Advanced optimal GWO-PID controller for DC motor - Ghada Adel Aziz; Salam Waley Shneen; Fatin Nabeel Abdullah; Dina Harith Shaker (Institute of Advanced Engineering and Science, 2022)
The current work aims to use traditional control algorithms and advanced optimization algorithms that was chosen for its ease of control and the possibility of using it in many industrial applications. By setting the appropriate specifications for the simulation model and after conducting the planned tests that simulate different applications of the motor’s work within electrical systems, the results proved to obtain good performance of the motor’s work, better response, high accuracy, in addition to the speed. The goal is to design and tune a proportional–integral–derivative (PID) controller by grey wolf optimization (GWO) using transfer function (T.F) for a direct current (DC) motor. To adjust the parameters of the traditional controllers using the optimum advanced, an appropriate mechanism and technology from the advanced optimization techniques were chosen, as the gray wolf technology algorithm was chosen as an optimization technique and integral time absolute error (ITAE) to adjust the parameters of the traditional PID controller.